Asociación entre patrones queiloscópicos, factores biológicos y condiciones labiales en estudiantes universitarios de Ciencias de la Salud. - Vallejo Arias, Selena Emperatriz; Blacio Campos, Joselyn Del Rosario (My University, 2025)
Cheiloscopy is an emerging biometric technique that analyzes the unique patterns of lip grooves for human identification, similar to fingerprints. This study aimed to explore the association between cheiloscopic patterns, classified according to Suzuki and Tsuchihashi, and biological factors such as sex and blood group. Additionally, it evaluated the influence of associated conditions in lip regions (thickness, commissures, hydration, dryness, and cosmetic use) in university students studying health sciences A quantitative, observational, descriptive, and cross-sectional study was conducted with a sample of 221 students selected using non-probabilistic sampling. The results indicated that Type I' (incomplete grooves) and Type II (bifurcated grooves) patterns were the most frequent across the different lip zones.Statistical tests, specifically chi-square and Fisher's exact test (for cosmetic use), did not reveal significant associations between the predominant cheiloscopic patterns and sex, blood group, or associated conditions (p > 0.05). Therefore, the lip patterns appear to be independent of the analyzed biological and external factors, supporting the stability and uniqueness of cheiloscopy as a complementary tool in forensic biometric identification. Further research with larger and more diverse samples is recommended to strengthen the scientific evidence.
La queiloscopía es una técnica biométrica emergente que analiza los patrones únicos de los surcos labiales para la identificación humana, similar a las huellas dactilares. Este estudio tuvo como objetivo explorar la asociación entre los patrones queiloscópicos, clasificados según Suzuki Tsuchihashi, los factores biológicos de sexo, grupo sanguíneo, evaluación de la influencia de condiciones asociadas en regiones labiales (grosor, comisuras, hidratación, sequedad y uso de cosméticos) en estudiantes universitarios de ciencias de la salud. Se realizó un estudio cuantitativo, observacional, descriptivo transversal con una muestra de 221 estudiantes seleccionados mediante muestreo no probabilístico. Los resultados indicaron que los patrones Tipo I' (surcos incompletos) Tipo II (surco bifurcado) fueron los más frecuentes en las diferentes zonas del labio. Las pruebas estadísticas de chi-cuadrado, la prueba exacta de Fisher para el uso de cosméticos no evidenciaron asociaciones significativas entre los patrones queiloscópicos predominantes y el sexo, grupo sanguíneo o condiciones asociadas (p > 0,05). Por lo tanto, los patrones labiales son independientes de los factores biológicos externos analizados, respaldando la estabilidad y unicidad de la queiloscopía como herramienta complementaria en identificación forense biométrica. Se recomienda continuar con investigaciones en muestras más amplias diversas para fortalecer la evidencia científica.
Keywords: QUEILOSCOPIA; PATRONES LABIALES; GRUPO SANGUINEO; SEXO